2009
DOI: 10.1542/peds.2009-0434
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Resuscitation With Low Oxygen Causes Less Oxidative Stress, Inflammation, and Chronic Lung Disease

Abstract: Resuscitation of preterm neonates with 30% oxygen causes less oxidative stress, inflammation, need for oxygen, and risk of bronchopulmonary dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
367
2
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 430 publications
(391 citation statements)
references
References 53 publications
11
367
2
11
Order By: Relevance
“…Current revised neonatal resuscitation guidelines recommend starting resuscitation with air for the term and near-term infant, but there is still no consensus on which FiO 2 to administer to the preterm (10). Recent data (11) indicate lower oxidative stress and long-term lung injury after resuscitation of preterm born babies with 30 vs. 90% oxygen.…”
mentioning
confidence: 99%
“…Current revised neonatal resuscitation guidelines recommend starting resuscitation with air for the term and near-term infant, but there is still no consensus on which FiO 2 to administer to the preterm (10). Recent data (11) indicate lower oxidative stress and long-term lung injury after resuscitation of preterm born babies with 30 vs. 90% oxygen.…”
mentioning
confidence: 99%
“…Close to one third of responders start resuscitation with a delivered oxygen concentration of 30 to 50%, a practice that is supported by some recent small randomized controlled trials despite the fact these trials were not sufficiently powered to evaluate the impact on long-term outcome. [19][20][21][22] There is likely to be clinical equipoise until new evidence is provided or the recommendation is further modified. It is worth noting that 10% of respondents still use 100% oxygen to initiate resuscitation, which may induce hyperoxia and oxidative stress-mediated end-organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen restriction immediately after birth does not predispose to subsequent persistence of PDA. 58 A recent retrospective analysis suggested that lower target saturation ranges increased the prevalence of early hemodynamically significant PDA, but not the ultimate closure rate or need for surgical ligations. 59 No differences in PDA or medical or surgical treatment for PDA were observed in a randomized trial comparing target ranges of oxygen saturation of 85 to 89% or 91 to 95% in preterm infants between 24 and 27 weeks' gestation.…”
Section: Prolongation Of Ductal Patencymentioning
confidence: 99%